Potrzeby informacyjne i odpowiedzialność zarządzających w publicznych zakładach opieki zdrowotnej - Baran, Wioletta (The information needs and the responsibility of the management in public health care institutions, 2008)
The aim of this article was to identify the information needs and responsibility of the management in public health care institutions. Conducted researches consist in the assessment of responsibility accounting functioning conditions. The results, such as lack of delegations of decision-making entitlements and responsibility, deficiency in the budgeting process connected with the system of monitoring and control, showed that in the researching entity the responsibility accounting system does not exist.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 13-20